PERTOBATAN: MENGHASILKAN BUAH YANG BAIK: Analisa Biblis Kisah Yohanes Pembaptis (Matius 3: 1-12) - Suprianto, Edi; Pongoh, Damianus (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This article specifically examines and deepens the story of John the Baptist in Matthew 3:1-12. This text was chosen to examine more specifically how the story of effect or Wirkungsgeschichte of the text affects the Church's liturgy, particularly to examine the meaning of baptism and the vow of poverty in religious life. Often in reading Scripture, readers have difficulty grasping the implied meaning of a text. Therefore, the task of the exegete is to provide an interpretation for the needs of teaching faith. This article was written with the aim of finding the implied meaning of the text as part of the exegetical task to help readers discover and understand the meaning of the text that is familiar in the life of the faith of the people. The method used in this paper is text analysis based on the commonly used hermeneutic approach to Scripture. The novelty in this article is a new understanding of the meaning of baptism as a new birth. The new birth is not just an empty phrase or slogan, but baptism is a transition from the old life to a new life, namely as children of God. As a concrete expression of the new birth, it is repentance to produce good fruit, namely the values ​​of the Kingdom of God. In addition, this story also provides deep inspiration regarding the meaning of the Vow of Poverty in religious life through the simplicity of John the Baptist's life.